Conception and Implementation of a Dual Data Acquisition System on an Eight-Axis High-Speed Tube Cutting CNC Machine. (20th May 2010) - Chen, Zengshi; Gao, Wenzhong
Abstract : Precise and fast position measurement has been a challenging problem in computerized numerical controller (CNC) machines where parts need to be processed at a high speed. This paper inspects data acquisition and processing on a high-speed tube cutting Siemens 840D CNC machine with Windows NT.40 operating system and analyzes the constraints of the old procedure on the production speed. The more efficient technical tactics are proposed and implemented. The laser is added to the system to perform the same data acquisition while the function of the capacitive sensor is kept. A dual data acquisition system is thus created and the old one functions as a backup. In the retrofit, the affordable and practical data communication method is used, the sensor physical movement is avoided, the algorithm is optimized with requirement of less data, and computation of the algorithm is moved from numerical controller unit (NCU) to personal computer unit (PCU). For every tube part, the laser approach reduces the data acquisition and processing time to 4 seconds, compared to 12 seconds with a capacitive sensor.